Osmanlı Maarifi’nde musiki - Özden, Erhan (My University, 2013)
Nezareti, Maârif Nizamnamesi, Mûsikî Muallim Mektebi, Gına, Mülahazat, Mûsikî Muallimi, Mûsikî Talimatnamesi. ÖZET OSMANLI MAÂRİFİ’NDE MÛSİKÎ Başta Enderûn olmak üzere Mehter, Mevlevîhâneler ve Mızıkâyı Hümâyûn Osmanlı’da mûsikî eğitiminin verildiği kurumlardır. Tanzimat’tan sonra bu kurumlar arasına maârife bağlı okulların da girdiği görülmektedir. Sıbyan mektepleri, rüşdiye, idâdî, sultânî ve yüksek öğrenim mektepleri XIX. asrın sonlarına doğru mûsikî eğitimi vermeye başlamıştır. Yeni eğitim sisteminde yetişen mûsikî muallimleri meşk sistemine dayalı mûsikî öğrenimini artık çağın gerektirdiği plan, program ve imtihan düzenine göre vermektedirler. Bunun sonucunda yeni ders araç gereçleri, kaynaklar ve öğretim modelleri ortaya çıkmaktadır. Bu çalışmanın amacı Osmanlı Maârif teşkilatının mûsikî politikasını incelemek ve altı asır boyunca devam eden mûsikî eğitiminin özetini sunmaktır. Tanzimat’ın ilanından sonra tedrisata girmeye başlayan modern eğitim anlayışı mûsikî derslerine eskisinden daha çok önem vermektedir. Bu döneme ait ulaşabildiğimiz arşiv belgeleri dönemin mûsikî eğitimi hakkında önemli bilgiler vermektedir. Bu bilgiler ışığında imtihan, ders programları, tedrisat cetvelleri, muallim atama ve maaşları ve mûsikî araç-gereçleriyle ilgili elimizdeki belgelerden yola çıkarak Osmanlı Maârifi’nde mûsikînin serüvenini aktarmaya çalışacağız. stry of Education, Ministry Regulations, School Music Teachers, Gına, Mülahazat, Curriculum, Music Teacher, Music Ordinance, The Palace School.

MUSIC IN OTTOMAN EDUCATION Especially special school in the Ottoman Palace Janissary Band, lodge used by mevlevi dervishes and harmonica imperial are the institutions, in which music education is given in Ottoman Empire. schools connected to education take place between these institutions after the political reforms made in the ottoman state in 1839. Ottoman elementary –primary school, ottoman junior high school, high school and sultânîc and higher education schools started to give musical education towards the end of the 19th century. Music teachers educated in the new education system trained, the musical education dependent practice system, according to the logics of age plans ,programs and exam system anymore. So, ıt appears new lesson equipments, sources and educational models. The purpose of this study is analyzing the musical politics of ottoman education organization and surveying as a summary musical education continued throughout 6th century. The modern education perceptive started to take place in schooling after the political reforms made in the ottoman state in 1839 place emphasis on art lessons and music more than older time. The accessible archive records belonging to that time give important informations about musical education of age. So we try to narrate the adventure of music in ottoman education system with documents based on exam, curriculums, school programs, teachers assignment and payments and musical equipments and materials.
Keywords: İslam Dini; Musiki_İslam Dini; Müzik